(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2023)
A survey was conducted in the farmers’ orchards of 7 coastal districts, namely Patuakhali, Barguna, Barishal, Khulna, Bhola, Laxmipur, and Noakhali of Bangladesh to know the abundance of rugose spiraling whitefly on coconut and an experiment consisting of 5 treatments and an untreated control following RCBD with 3 replications was also carried out for controlling rugose spiraling whitefly at Patuakhlai Science and Technology University (PSTU) campus during January to May, 2022. Results revealed that the highest abundance (23 egg spirals, 34 nymphs, 31 adults per leaflet, respectively) of rugose spiraling whitefly was found at Khulna, followed by Noakhali (19 egg spirals, 31 nymphs, 27 adults per leaflet, respectively) while the lowest (9 egg spirals, 13 nymphs, 11 adults per leaflet, respectively) was in Patuakhali among 7 coastal districts. Although all insecticidal treatments (T1 = Tyfos 48 EC (Chlorpyrifos) @ 1 ml/L of water, T2= Caught 10 EC (Cypermethrin) @ 1 ml/L of water, T3 = Nitro 505 EC (Chlorpyrifos + Cypermethrin) @ 1 ml/L of water, T4= Fyfanon 57 EC (Malathion) @ 1 ml/L of water, T5= Bioclean @ 1 ml/L of water) effectively reduced the different stages of rugose spiraling whiteflies compared to untreated control, the lowest mean number of egg spirals (0.00), nymphs (0.11) and adults (0.11) per leaflet were obtained by the application of Nitro 505EC @ 1 ml/L of water followed by Bioclean @ 1 ml/L of water at 3 DAS. The highest percent reduction of egg spirals (100%), nymph (98.82%), and adult (98.79%) of whitefly population over control were also obtained by the application of Nitro 505EC @ 1 ml/L of water followed by Bioclean @ 1 ml/l of water at 3 DAS. These two chemicals were found to be very effective for controlling rugose spiraling whiteflies. Considering environmental safety, Bioclean @ 1 ml/L of water is recommended to use against this pest as an eco-friendly approach for safe food production. J. Asiat. Soc. Bangladesh, Sci. 49(2): 165-177, December 2023